Marketing substantiation of expediency of new domestic acne medicines development - Shablii , Liubov (Problems of Environmental Biotechnology, 2021)
Acne is a common chronic inflammatory skin disease that dramatically reduces the quality of life of patients, can lead to the appearance of cosmetic defects and disorders of the psycho-emotional sphere. The aim of the work was to study the Ukrainian pharmaceutical market of dermatological medicines for acne pharmacotherapy. For the study, official sources of information about medicines registered in Ukraine were used. The full range of dermatological medicines includes 587 trade names. The D10 “Acne Treatment Medicines” Group consists of 23 brand names, of which 17 are topical (D10A) and 6 medicines are intended for systemic treatment (D10B). It was determined that 76.5% of the D10A group medicines and 100% of the D10B group medicines are foreign drug products.